2012
DOI: 10.1136/gutjnl-2012-302759
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus erlotinib followed by capecitabine versus capecitabine plus erlotinib followed by gemcitabine in advanced pancreatic cancer: final results of a randomised phase 3 trial of the ‘Arbeitsgemeinschaft Internistische Onkologie’ (AIO-PK0104)

Abstract: Objective AIO-PK0104 investigated two treatment strategies in advanced pancreatic cancer (PC): a reference sequence of gemcitabine/erlotinib followed by 2nd-line capecitabine was compared with a reverse experimental sequence of capecitabine/erlotinib followed by gemcitabine. Methods 281 patients with PC were randomly assigned to 1st-line treatment with either gemcitabine plus erlotinib or capecitabine plus erlotinib. In case of treatment failure (eg, disease progression or toxicity), patients were allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 34 publications
3
70
0
3
Order By: Relevance
“…This was in contrast to the modest improvement in overall survival of 0.33 months with the gemcitabine/erlotinib combination, the only regimen prior to FOLFIRINOX that improved survival compared to gemcitabine (median overall survival of 6.24 months with gemcitabine/erlotinib and 5.91 months with gemcitabine). 16,17 Analysis indicated that the survival benefit of FOLFIRINOX was not due to use of subsequent second-line therapy. All subgroups favored FOLFIRINOX for improved survival, except for those with metachronous metastases, 3 or more metastatic sites or a biliary stent, who favored gemcitabine monotherapy.…”
Section: First-line Systemic Treatment For Advanced Pancreatic Cancermentioning
confidence: 99%
“…This was in contrast to the modest improvement in overall survival of 0.33 months with the gemcitabine/erlotinib combination, the only regimen prior to FOLFIRINOX that improved survival compared to gemcitabine (median overall survival of 6.24 months with gemcitabine/erlotinib and 5.91 months with gemcitabine). 16,17 Analysis indicated that the survival benefit of FOLFIRINOX was not due to use of subsequent second-line therapy. All subgroups favored FOLFIRINOX for improved survival, except for those with metachronous metastases, 3 or more metastatic sites or a biliary stent, who favored gemcitabine monotherapy.…”
Section: First-line Systemic Treatment For Advanced Pancreatic Cancermentioning
confidence: 99%
“…41,42 To assess whether KRAS mutations conferred resistance to erlotinib therapy in pancreatic cancer, posthoc analyses were performed of the PA.3 trial and a second trial involving erlotinib, known as AIO-PK0104 (Arbeitsgemeinschaft Internistische Onkologie -PK0104). 38,43 The latter trial compared gemcitabine followed by capecitabine at disease progression with capecitabine followed by gemcitabine at disease progression, with erlotinib administered in the first-line regimen in both arms. Unfortunately, these subgroup analyses had modest power and failed to show statistically significant interactions between somatic KRAS mutations and patient survival while receiving erlotinib.…”
Section: Rubinson and Wolpinmentioning
confidence: 99%
“…capecitabine, oxaliplatin, irinotecan and cisplatin), small molecule inhibitors or monoclonal antibodies against receptor tyrosine kinases or oncogenic growth factors. Unfortunately, despite promising results in preclinical approaches, none of these combinations were able to significantly prolong progression free or overall survival when compared with gemcitabine monotherapy [2,3,4,5,6]. …”
Section: Established First-line Treatment Concepts In Metastatic Pdacmentioning
confidence: 99%